Moringa oleifera, Basella Rubra Linn, Corchorus olitorius Vegetable Jellies: Potentials for Product Development and Commercialization - Olano, Leila (JPAIR Multidisciplinary Research, 2016)
Naturally-made products are now available in the local and international markets. Green leafy vegetables are very rich in phytonutrients that could be utilized in producing value-added products like vegetable jellies. The study considered green leafy vegetables: Malunggay (Moringa oleifera), Kulitis  (Amaranthus spinosus L.), Camote tops (Ipomoea batatas), Alugbati (Basella Rubra Linn),Saluyot (Corchoru solitorius) for the development of vegetable jellies. It specifically determined the sensory acceptability of vegetable jellies in terms of their appearance, aroma, color, texture, consistency, and general acceptability using the single factor experiment in a Completely Randomized Design considering five treatments evaluated by 80 evaluators using score cards for sensory evaluation. The appearance, aroma, texture, consistency and general acceptability of Malunggay jelly was "Liked Very Much" while Saluyot jelly was "Liked Extremely" in terms of color. There were significant differences among the vegetable jellies in the sensory qualities and general acceptability of Malunggay jelly and Saluyot jelly in terms of color. The five vegetable jellies were acceptable. Malunggay jelly had the highest acceptability that was high in ash, crude protein, crude fat, carbohydrates and energy content. Saluyot jelly was high in moisture content, and Alugbati jelly was high in sodium content. Malunggay (Horseradish tree), Alugbati (Malabar nightshade), and Saluyot (Jute leaves) vegetables have potentials for product development as vegetable jellies.
Keywords: Science and clinical laboratory; vegetable jelly; nutrition; CRD; experimental design; Capiz; Philippines